\(\frac{2}{3}-\left(\frac{1}{6}+\frac{1}{8}\right)\)=\(\frac{16}{24}-\left(\frac{4}{24}+\frac{3}{24}\right)\)=\(\frac{16}{24}-\frac{7}{24}=\frac{9}{24}=\frac{3}{8}\)
2/3 - ( 1/6 + 1/8 ) = 2/3 - 7/24 = 3/8
4 2/3 + 2 3/4 . 7 3/11 = 14/3 + 11/4 . 80/11 = 14/3 + 20 = 74/3
2 1/10 - 3/4 - 2/5 = 21/10 - 3/4 - 2/5 = 21/10 - ( 3/4 + 2/5 ) = 21/10 - 23/20 = 19/20
2 - x = 4/7
x = 2 - 4/7
x = 10/7
3/5 . 4/7 . 1 1/2 = 3/5 . 4/7 . 3/2 = 18/35
x . 2/5 = 4/7
x = 4/7 : 2/5
x = 10/7
x : 6/11 = 44/9
x = 44/9 . 6/11
x = 2/3
\(\frac{2}{3}-\left(\frac{1}{6}+\frac{1}{8}\right)=\frac{2}{3}-\left(\frac{4}{24}+\frac{3}{24}\right)=\frac{2}{3}-\frac{7}{24}=\frac{16}{24}-\frac{7}{24}=\frac{9}{24}=\frac{3}{8}\)
\(2\frac{1}{10}-\frac{3}{4}-\frac{2}{5}=\frac{21}{10}-\frac{3}{4}-\frac{2}{5}=\frac{42}{20}-\frac{15}{20}-\frac{8}{20}=\frac{42-15-8}{20}=\frac{19}{20}\)
\(2-x=\frac{4}{7}\)
\(\Rightarrow x=2-\frac{4}{7}\)
\(\Rightarrow x=\frac{10}{7}\)
\(\frac{3}{5}\times\frac{4}{7}\times1\frac{1}{2}=\frac{3}{5}\times\frac{4}{7}\times\frac{3}{2}=\frac{3\times4\times3}{5\times7\times2}=\frac{18}{35}\)
\(x\times\frac{2}{5}=\frac{4}{7}\)
\(\Rightarrow x=\frac{4}{7}\div\frac{2}{5}\)
\(\Rightarrow x=\frac{4}{7}\times\frac{5}{2}\)
\(\Rightarrow x=\frac{10}{7}\)
\(x\div\frac{6}{11}=\frac{44}{9}\)
\(\Rightarrow x=\frac{44}{9}\times\frac{6}{11}\)
\(\Rightarrow x=\frac{8}{3}\)
6-|1/2-x|=2/5